Effect of Crop Geometry on Growth, Yield and Quality of Sweet Potato (Ipomoea batatas L.) Genotypes - Prakash Bhattarai; Kalyani Mishra Tripathi; Durga Mani Gautam; Arjun Kumar Shrestha (Turkish Journal of Agriculture: Food Science and Technology, 2022)
Field experiments were conducted in 2018 and 2019 at the National Potato Research Programme (NPRP), Lalitpur (1360 masl), Nepal, to determine the effect of crop geometry on the growth, yield, and quality of sweet potato genotypes. The experiment was laid out on sandy loam soil in a factorial randomized complete block design (RCBD) with three replications and comprised of a total of twelve treatment combinations of four crop geometry (60cm×25 cm, 60cm×30 cm, 70cm×25 cm, and 70cm×30 cm) and three genotypes (CIP 440015, CIP 440267 and Local White). Among the different crop geometries and genotypes evaluated, 70cm×30 cm plant spacing and Local White genotype were found statistically superior to enhance marketable tuberous root weight per plant (0.572 and 0.541 kg), tuberous root diameter (62.59 and 61.0 mm), shoot fresh weight (509 and 524 g), and tuberous root yield per plant (616 and 620 g). The genotype, Local White yielded higher among the genotypes. The reducing sugar content was influenced significantly by crop geometry and genotypes. The pooled mean showed the highest (15.48 and 17.26 %) reducing sugar in closer geometry 60 cm × 25 cm and Local White genotype respectively and the lowest (11.54 %) in the genotype CIP 440015. CIP genotypes, on the other hand, were high in ß carotene content, whereas the Local genotype had a negligible amount (0.35 mg/100g). On hectare level, our result showed that highest plant density of 66,666 plants ha-1 (60 cm × 25 cm) could give the highest yield per unit area due to greater crop biomass. Our findings suggest that crop geometry can have a considerable impact on sweet potato production. As a result, the geometry of sweet potatoes can be wide or narrow depending on our needs and the area available in our study area or a similar situation.